Resilient healthcare theory as a lens to research emergency department operations: a protocol for a scoping review. Issue 12 (30th December 2021) - Chessum, Peter Thomas; Sujan, Mark; Xyrichis, Andreas; Anderson, Janet E
Abstract : Introduction: Emergency departments (EDs) are complex systems that have constant fluctuations in demand, creating mismatches with planned capacity. Despite the complexity of ED operations, quality and safety improvement are often approached in a reactive, linear and reductionist manner. There is increasing interest in adopting Resilient Healthcare (RHC) techniques based on complex systems thinking as a method for quality improvement and research in EDs. However, the evidence for this approach is still developing and it is not clear what techniques have been used so far and which are most effective. This scoping review will be conducted between March 2022 until May 2022. It seeks to examine the international literature for available reports that have adopted RHC theory to study ED operations and identify approaches used and proposed benefits. Methods and analysis: The methodology for scoping reviews outlined by Arksey and O'Malley (2005) will be followed, acknowledging refinements made to the scoping review process by Levac et al (2010). The methodology consists of five steps: (1) identifying the research question; (2) identifying the relevant literature; (3) study selection; (4) charting the data; and (5) collating, summarising and reporting the results. A two-stage approach will be undertaken to synthesise and report results: (1) numerical analysis of the nature and distribution of studies (the overall number of studies, country of origin, the most studied core function of ED, type of research design); and (2) a thematic mapping of the literature. Ethics and dissemination: Scoping review methodology synthesises published data and, therefore, does not require ethical approval. An article formatted in line with Preferred Reporting Items for Systematic Reviews and Meta-Analyses forScoping Reviews reporting guidance will be submitted for publication to a scientific journal. Findings will also be presented at relevant advanced practice conferences and disseminated within clinical and academic groups.